The Synergistic Effect of Urban Canyon Geometries and Greenery on Outdoor Thermal Comfort in Humid Subtropical Climates - Peng, Mingxi; Huang, Haijing (Frontiers in Environmental Science, 2022)
Understanding the synergistic effect of multiple parameters is helpful to urban planners trying to design sustainable cities through a holistic approach. The objective of this research was to investigate how the street aspect ratio (HW), street orientation (AO), and greenery parameters, such as leaf area density (LAD) and aspect ratio of trees (ART), could affect the microclimate and outdoor thermal comfort of street canyons in a central business district under the local climate conditions of Chongqing city. To achieve this goal, a series of single- and multi-parameter simulations which followed an orthogonal design of experiments (ODOE) were conducted. The physiological equivalent temperature (PET) was adopted to assess the results of microclimate simulations for different urban models. The main findings are as follows: 1) The aspect ratio and orientation of urban canyons and ART play significant roles in influencing microclimate variables at the pedestrian level. 2) There is an inverse relationship between the street aspect ratio and Tmrt, and likewise for ART; the highest wind velocity was obtained when the aspect ratio of canyons was 2 and 3, which consequently developed the channeling phenomenon (when the domain wind is prevailing with street direction). 3) The East–West streets and canyons with an HW = 0.5 incur the warmest thermal conditions and longest extreme discomfort durations. 4) Results for the PET and meteorological parameters exhibit less significant variation obtained from different values of LAD than those observed in the other three parameters.